Developing a PMRI-guided learning trajectory for elementary students’ understanding of percentages within the melemang cultural context - Arbella Sri Marleny M; Zulkardi; Ratu Ilma Indra Putri; Yusuf Hartono (CV. FOUNDAE, 2026)
Background: Understanding percentages poses persistent challenges for elementary students, particularly when the percent symbol is interpreted as a standalone number rather than as a relational expression of “per hundred.” Instruction that is detached from meaningful contexts often restricts students’ ability to connect percentages with fractions and decimals. Aims: Responding to this issue, the study seeks to develop and validate a PMRI-guided learning trajectory that situates percentage concepts within the local cultural practice of melemang. Method: Employing design research of the validation study type, the study involved 28 elementary students and was conducted in three phases: preliminary design to formulate a Hypothetical Learning Trajectory (HLT), teaching experiment to implement and observe the instructional sequence, and retrospective analysis to refine the HLT into an empirically grounded Actual Learning Trajectory (ALT). Data from classroom observations, student work, interviews, and video recordings were analyzed qualitatively to examine students’ conceptual development. Results: The findings indicate that engaging students with the melemang context enabled them to interpret percentage as a comparison to one hundred. Through a structured progression from concrete representations to bar models and 100-grids, students established meaningful connections among fractions, decimals, and percentages. Conclusion: The resulting learning trajectory demonstrates how culturally grounded PMRI-based instruction can support coherent conceptual development and inform context-sensitive mathematics teaching practices.